Global strategic management - Lasserre, Philippe; Monteiro, Felipe (New York Bloomsbury Academic, 2022)
"Global Strategic Management is a textbook that is targeted at discrete modules on Global Strategic Management. It provides a user-friendly yet comprehensive introduction to planning and making decisions for businesses on a global scale and is supported by ample pedagogical features, including many case studies and examples featuring an interesting mix of both established multinational companies and more unknown SMEs still developing their international presence. Lasserre is a highly regarded text and well-recognised for its ability to seamlessly blend academic rigour and practicality, making it one of the most accessible and engaging texts, one which students enjoy and from which they find it easy to learn. For this fifth edition, the author Philippe Lasserre has been joined by author Felipe Monteiro. Together they have written the 5th edition of Global Strategic Management"--
Revised edition.
Includes bibliographical references and index.
Keywords: International business enterprises -- Management; Strategic planning; Globalization -- Economic aspects